Recent Recovery of the World’s Rarest Primate Is Not Directly Linked to Increasing Habitat Quality - Zou, Yike; Turvey, Samuel T.; Cui, Jie; Zhang, Hui; Gong, Wenfeng (Frontiers in Ecology and Evolution, 2022)
Due to habitat loss, Hainan gibbon (Nomascus hainanus), the world’s rarest primate, has only two social groups and seven known individuals in 1978. On account of establishing Bawangling National Natural Reserve (BNNR) to increase habitat area from 56 km2 in 1980 to 300 km2, Hainan gibbon has five groups and 35 individuals in 2021. Thus it is important to quantify whether the largely increased habitat area indeed resulted in increased Hainan gibbon population dynamics. However, this seems difficult to be implemented, as Hainan gibbon is strictly dependent upon continuous natural tropical broadleaf forest from 400 to 1300 m in BNNR and we are lacking in accurate information on natural tropical broadleaf forest distribution in BNNR. Here by using 21-year artificial tracing of Hainan gibbon and plot surveying in 2021, we attain the most accurate boundary for natural tropical broadleaf forest across the BNNR landscape from 400 to 1300 m and within the home range for each of the five social groups for Hainan gibbon. We then utilized Landsat time series images and time-series analysis to compute nonlinear causal relationships between natural tropical broadleaf forest dynamics across the BNNR landscape from 400 to1300 m and within the home range of each group and gibbon population dynamics from 2000 to 2021. Natural tropical broadleaf forest dynamics include total forest area and forest fragmentation, whereas gibbon population dynamics are variation in total number of individuals for the entire gibbon population and within each social group, and variation in total number of social groups). Finally, two new findings have been attained. First, due to specific reproductive behavior, a one-year time lag of population response, instead of an instantaneous population response to improved habitat quality would be expected. Second, largely improved Hainan gibbon habitat quality is not the direct determinants of the recovery of Hainan gibbon.